2023
DOI: 10.1073/pnas.2212154120
|View full text |Cite
|
Sign up to set email alerts
|

Emotional (in)stability: Neuroticism is associated with increased variability in negative emotion after all

Nina Mader,
Ruben C. Arslan,
Stefan C. Schmukle
et al.

Abstract: The personality trait neuroticism is tightly linked to mental health, and neurotic people experience stronger negative emotions in everyday life. But, do their negative emotions also show greater fluctuation? This commonsensical notion was recently questioned by [Kalokerinos et al. Proc Natl Acad Sci USA 112, 15838–15843 (2020)], who suggested that the associations found in previous studies were spurious. Less neurotic people often report very low levels of negative emotion,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 26 publications
3
18
0
Order By: Relevance
“…Of the personality traits, neuroticism was most predictive of the self-organizing dynamics of body motion (RQA) measures. More neurotic participants were more likely to show unpredictable, unstable, less complex, and more fluctuating/volatile motion dynamics (thus low emotional stability), in line with H2b and the literature (e.g., Mader et al, 2023). These effects were observed when talking about sensory experiences (topic 2) and were most pronounced when participants talked about their socio-emotional life (topic 3).…”
Section: Personality Differences and Their Modulation Of Self-organiz...supporting
confidence: 84%
See 1 more Smart Citation
“…Of the personality traits, neuroticism was most predictive of the self-organizing dynamics of body motion (RQA) measures. More neurotic participants were more likely to show unpredictable, unstable, less complex, and more fluctuating/volatile motion dynamics (thus low emotional stability), in line with H2b and the literature (e.g., Mader et al, 2023). These effects were observed when talking about sensory experiences (topic 2) and were most pronounced when participants talked about their socio-emotional life (topic 3).…”
Section: Personality Differences and Their Modulation Of Self-organiz...supporting
confidence: 84%
“…Extraversion as most expressible personality factor (e.g., Albright et al, 1988;Kenny et al, 1992;Jiang et al, 2023) captures differences in flexibility, novelty seeking (DeYoung, 2013), and resilience (Oshio et al, 2018), and high scorers were expected (H2a) to show adaptive selforganizing behavior as indicated by more system Entropy (complexity/flexibility), Determinism, Laminarity, and Mean Line. Neuroticism captures more unstable patterns of body motion (Koppensteiner, 2013) and emotion dynamics (Mader et al, 2023). Neuroticism was expected (H2b)…”
Section: Current Studymentioning
confidence: 92%
“…In the present study, even with only the single outcome of health status, sigma proved to have predictive utility above and beyond any associations attributable to intercepts and slopes. This finding corresponds with past research that has examined more short-term, dynamic within-person variability metrics from intensive longitudinal data and found that these metrics are likewise unique predictors of poorer health outcomes, particularly mental health (Anvari et al, 2023;Mader et al, 2023;Ringwald & Wright, 2024). The effects in the present study, as well as in any study in which personality metrics are used to predict an outcome, highlight an important point.…”
Section: Predictionsupporting
confidence: 90%
“…3 Another alternative was proposed by Mestdagh et al (2018), who suggested the use of a relative variability index that takes into account the maximum possible variance given an observed mean. However, this approach was subsequently criticized by Mader et al (2023), who argued that the relative variability index and other corrective indices do not consider the assumed mechanism of data generation and the theoretical possibility of emotional states outside the scale bounds (e.g., extremely positive affective states beyond the upper end of the scale). They suggested a Bayesian-censored location scale model (BCLS) as an alternative modeling approach, which offers the advantages of a MELS model and additionally treats observed affective states as censored variables (i.e., true affective states are assumed to follow an unbounded normal distribution that is censored during the measurement process due to scale bounds).…”
Section: The Conflation Of Mean Affect Levels and Affect Variabilitymentioning
confidence: 99%